The Improving Of Children's Cognitive Ability On Demonstration Method Of Origami Crease - Asmuddin, Asmuddin; Salwiah, Salwiah (Universitas Negeri Semarang, 2021)
The improving of children's cognitive ability through demonstration method of origami crease in wulele sanggula at group B state of kindergarten 2. This study aims to improving of children's cognitive ability through demonstration method of origami crease in wulele sanggula at group B state of kindergarten 2. This type of the research is Classroom Action Research. This research was conducted in two cycles. The stages in this study follows the classroom action research procedures, namely: (1) planning, (2) implementation the action, (3) observation and (4) reflection. The subjects in this study were teachers and childrens in Wulele Sanggula at Group B State of Kindergarten 2, totaling 15 children consist of 6 girls and 9 boys. Based on the analysis of data from teacher teaching activities at the first cycle in amounting 15 aspects getting percentage of achievement in the amount of 86,66% or 13 aspect that achieved, the children's learning activityat the first cyclefrom 15 aspect getting percentage of achievement in the amount of 80% or 12 aspect that achieved and from the children's learning in improving of children's cognitive ability through demonstration method of origami crease getting percentage of achievement in the amount of 66,67% or10 students. The result of teacher teaching activities at the second cycle increasing by getting percentage of achievement in the amount of 93,33% or 14 aspect that achieved, and the result of children's learning to improving of children's cognitive ability through demonstration method of origami crease getting percentage of achievement in the amount of 86,66%. Thus it can be concluded that children's cognitive abilitycan be improving through demonstration method of origami crease in wulele sanggula at group B state of kindergarten 2.